Renal ewing sarcoma in a young female: a case report and review of targeted therapy - Pengfei Wang; Mingfa Wang; Jiangtao Zhan; Xinming Hu; Xusong Meng (Frontiers in Surgery)
Ewing sarcoma (ES) is an aggressive neoplasm predominantly affecting pediatric and adolescent populations. Renal involvement in ES is exceedingly rare, representing less than 1% of all renal malignancies. Herein, we present the case of a 22-year-old female diagnosed with renal Ewing sarcoma (RES) accompanied by renal vein thrombosis. The patient reported a one-month history of persistent left lumbar pain, prompting hospitalization. Magnetic resonance imaging identified an extensive left suprarenal mass measuring 13.5 × 10.5 × 4.5 cm, with concurrent renal vein thrombosis. The comprehensive evaluation of histopathology, immunohistochemistry and molecular genetics confirmed RES. The treatment included radical left nephrectomy, followed by adjuvant chemotherapy (i.e., vincristine, epirubicin and cyclophosphamide) after surgery. Genetic analysis of the tumor revealed mutations in P53 and STGA2. Follow-up contrast-enhanced computed tomography scans of the patient demonstrated metastatic progression to the pancreas. The patient passed away after a 7-month follow-up period. This article reviews our treatment experience and recent developments in targeted therapies. Aiming to provide new approaches for the treatment of RES, this combines next-generation sequencing technology with targeted therapy to promote the optimization of targeted treatments.